Integration of Sharia and Conventional Financial Instruments in Achieving Inclusive Economic Development - Layyinatus Shifah; Isnaini Harahap (Universitas Kristen Indonesia Toraja, 2024)
Islamic finance has increased rapidly lately. The increase is due to the fact that people are starting to use sharia and Islamic principles in transactions because they prioritize ethics and morals. The rapid development of course there are still challenges faced, one of which is about the less massive use by the community. This certainly needs to be studied again, such as the integration between Islamic financial instruments and conventional finance so that there can be an inclusive collaboration in the financial world. This research uses an analytical description method with secondary data sources. The results of this study indicate that the role of Islamic finance on economic development is very significant, this is because the principles of sharia prioritize ethics and morals in transactions so that people trust more than conventional finance. With an increasing role, of course there are still obstacles faced, one of which is limited public access to Islamic finance and an integration with conventional finance is needed. With integration with conventional finance, it turns out to be able to realize an inclusive economy such as the presence of Islamic capital markets, Islamic banking, and others so as to bring up other alternatives in the financial world.